Students’ Ability in Answering Questions of Each Section in the TOEFL - M. Fadhly Farhy Abbas (ELT-Lectura, 2016)
This research is based on the needs analysis as well as to evaluate the students’ ability inanswering the questions in TOEFL. This is done because the score of TOEFL is used as one of therequirement to join thesis exam at English Education Department, Faculty of Teachers Training andEducation University of Lancang Kuning. This research aims at analyzing the students’ ability in answeringTOEFL test. The method employed in this research was quantitative method with descriptive quantitativeresearch design. The population of this research were the students at the 7th semester which were consisted of55 students. All the population became the sample of this research. In this research, the researcher collectedthe data by using the TOEFL test. Then, the result of the test was analyzed by using scoring guideline inTOEFL, then the scores were categorized into some levels of ability. The result of the test showed that thescores obtained by the students were mostly under 450 and categorized into low level ability (ExtremelyLimited User). It can be concluded that the students’ ability in taking TOEFL test is categorized into lowlevel ability.